Development Of Cognitive Abilities Of Children 3-7 Years Old - Hasanova Iroda Olimjonovna (Academia One, 2024)
The article reveals age-related features of the development of cognitive abilities of preschool children, significant progress in the cognitive development of children, as well as the use of various gaming methods in the development of children's cognitive abilities.
Keywords: preschool age; child; perception; play